Fundamentals of Clinical Practice
XXX, 837 p.
Keywords: Fundamentals of Clinical Practice, Second Edition presents medical students with a comprehensive guide to the social ramifications of a physician's work, and more experienced practitioners with the tools to augment their own patient-centered techniques.